Unemployment in India: Its types and Causes: Impact of Technological Advancements on Unemployment in Underdeveloped Countries (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The present paper focused on unemployment in India its types and causes of unemployment in underdeveloped countries. Unemployment means that while the human beings are inclined to working they have no work to do. The maximum important motives of India’s poverty and backwardness are her trouble of unemployment. The advancement in current generation has invented such machines, robots and computers, which could carry out the paintings of hundreds of individuals by me. These machines need most effective one or operators and therefore they seize bread from the hands of heaps of individuals. So this sort of technical advancement has also annoyed the trouble of unemployment. Our authorities have to adopt automation in one of these prudent ways that this hassle may be solved. The major reason of unemployment and underemployment in underdeveloped nations like India is the deficiency of the stock of capital with regards to the needs of the developing labor force within the modern international, man with the aid of himself can hardly produce whatever. Even the primitive guy wished a few elementary tools like the bow and arrow to have interaction in attempting to find the incomes of his livelihood